2018
DOI: 10.19044/esj.2018.v14n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Effective Internal Control Structure in Achievement of Targeted Success in Businesses

Abstract: Due to economic relations evolving over time, technology and changing business environments, the way in which one of the management functions, "control", is executed has undergone a number of changes. Accordingly, the management of a business has become unable to control operations directly, making it a necessity for businesses to obtain timely and reliable data for a number of purposes, including protecting assets, and eliminating or minimizing errors and frauds. Internal control structures, formed within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Muthusi (2017)concluded that various controls have to be established at diverse levels since the control by the management board alone is not enough to ensure the effective functioning of the risk monitoring system due to management board members do not have proper time to control over the organization. Hence, the management board should appoint an independent unit which is responsible for internal supervision (Turedi & Celayir, 2018;Waheed, Kaur, & Kumar, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Muthusi (2017)concluded that various controls have to be established at diverse levels since the control by the management board alone is not enough to ensure the effective functioning of the risk monitoring system due to management board members do not have proper time to control over the organization. Hence, the management board should appoint an independent unit which is responsible for internal supervision (Turedi & Celayir, 2018;Waheed, Kaur, & Kumar, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mengoptimalkan sumber daya teknologi informasi dan komunikasi tidak terlepas dari penciptaan struktur organisasi yang baik karena hal tersebut merupakan fungsi dari strategi dan investasi suatu organisasi karenanya desainnya perlu memperhatikan faktor-faktor pragmatis seperti gaya manajemen, budaya organisasi, kualitas sumber daya manusia, dan sistem penghargaan agar berdampak pada peningkatan kinerja organsasi (Mithas & Rust, 2016). Dengan demikian internalisasi organisasi menjadi penting, beberapa penelitian menunjukkan bahwa pengendalian internal yang efektif dapat mengurangi berbagai risiko kemungkinan inefisiensi investasi, melindungi aset dan mengurangi resiko kecurangan (Dhaliwal, Hogan, Wilkins, & Wilkins, 2011) (Li, Peters, Richardson, & Watson, 2012) (Turedi & Celayir, 2018). Investasi TI dapat meningkatkan efektivitas pengendalian internal, adaptasi terhadap TI dan proses strategi bisnis serta peran sumber daya manusia dapat meningkatkan pengendalian intern (Cao, Chen, Lin, Liu, & Zhang, 2017).…”
Section: Pendahuluanunclassified
“…Furthermore, Turedi and Celayir (2018) found that effective internal control structure is a crucial element in ensuring efficiency, profitability and sustainability across businesses and that effective control structure is the key to success desired/aimed for a business. Dubihlela and Nqala (2017) found that internal risk control mitigate risks and ensure the reliability of performance reports and compliance with laws, policies and regulations, thus enhance firm performance.…”
Section: Non-financial Performancementioning
confidence: 99%